2021
DOI: 10.1002/solr.202100422
|View full text |Cite
|
Sign up to set email alerts
|

Spray‐Coated Lead‐Free Cs2AgBiBr6 Double Perovskite Solar Cells with High Open‐Circuit Voltage

Abstract: Lead‐free Cs2AgBiBr6 double perovskite is considered a promising alternative photovoltaic absorber to the widely used lead halide perovskite due to its easy processability, high stability, and reduced toxicity. Herein, for the first time spray processing for the deposition of Cs2AgBiBr6 double perovskite thin films is reported. Microstructural (X‐ray diffraction, scanning electron microscopy) and optoelectronic (absorbance, photoluminescence, photocurrent density versus applied voltage curves, electrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 39 publications
4
52
0
Order By: Relevance
“…As shown in Figure 1c, the results are matchable to the J-V curves, which are also in accordance with the enhanced optical absorption of Cs 2 AgBiBr 6 perovskite films (Figure S2, Supporting Information). By carefully comparing the results with previously reported works, [21,34,45] the IPCE values for the control device are similar, an indicator of the considerable perovskite film with this solution-processable fabrication technology. Furthermore, the statistical distribution box diagram of the measured PCEs from random 12 PSCs with different PMMA concentrations is shown in Figure 1d.…”
Section: Resultssupporting
confidence: 69%
“…As shown in Figure 1c, the results are matchable to the J-V curves, which are also in accordance with the enhanced optical absorption of Cs 2 AgBiBr 6 perovskite films (Figure S2, Supporting Information). By carefully comparing the results with previously reported works, [21,34,45] the IPCE values for the control device are similar, an indicator of the considerable perovskite film with this solution-processable fabrication technology. Furthermore, the statistical distribution box diagram of the measured PCEs from random 12 PSCs with different PMMA concentrations is shown in Figure 1d.…”
Section: Resultssupporting
confidence: 69%
“…Most reports on double perovskites have focused on nanocrystals 8−11 or solution-based processes where powders are obtained through a filtering and drying process. 12−14 Specifically for Cs 2 AgBiBr 6 , only few studies have shown thin films of double perovskites formed through the traditional spin-coating process, 3,15,16 where low solubility of precursors hampered the synthesis of dense, thick films. 15,17,18 In this respect, dry, vapor-based processes are preferred for Cs 2 AgBiBr 6 .…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that no precursor traces or secondary phases such as Cs 3 Bi 2 Br 9 or Cs 2 AgBr or Cs 3 AgBr 2 are present in the thin films, postannealing of at least 250 C has to be applied. While the annealing temperature can be slightly reduced to 200 C by vacuum-assisted annealing beforehand, [54] other techniques such as laser assisted (at 200 C process temperature), [55] spray coating, [56] and vapor-assisted deposition [15,28,[57][58][59] demand for high annealing temperatures and yield power conversion efficiencies of only up to 1.41% in solar cells. The most commonly used technique, however, is spin coating during which the double perovskite solution (usually with concentrations of 0.5-0.6 M) is dropped quickly on a fastspinning substrate.…”
Section: The Role Of Fabrication Methodsmentioning
confidence: 99%